2009
DOI: 10.1007/s00253-008-1838-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-1,3-galactosyl-N-acetylhexosamine phosphorylase from Propionibacterium acnes

Abstract: Homologs of the beta-1,3-galactosyl-N-acetylhexosamine phosphorylase (GalHexNAcP) gene (gnpA) were cloned from the genomic DNA of Propionibacterium acnes JCM6425 and P. acnes JCM6473, showing 99.9% and 97.9% nucleotide sequence identity, respectively, with the ppa0083 gene from the genome-sequenced P. acnes KPA171202. No gnpA gene was detected in the genomic DNA of type strain P. acnes ATCC25746. The recombinant enzyme from P. acnes JCM6425 (GnpA) showed approximately 70 times higher specific activity of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…To date, GalHexNAcP is the only phosphorylase known to act on ␤-galactoside. This enzyme was first found in the cell-free extract of Bifidobacterium bifidum (14) and then in B. longum (1,15), Clostridium perfringens (16), Propionibacterium acnes (17), and Vibrio vulnificus (18). These studies revealed that GalHexNAcPs were classified into three subgroups based on substrate preference between GNB and LNB.…”
mentioning
confidence: 99%
“…To date, GalHexNAcP is the only phosphorylase known to act on ␤-galactoside. This enzyme was first found in the cell-free extract of Bifidobacterium bifidum (14) and then in B. longum (1,15), Clostridium perfringens (16), Propionibacterium acnes (17), and Vibrio vulnificus (18). These studies revealed that GalHexNAcPs were classified into three subgroups based on substrate preference between GNB and LNB.…”
mentioning
confidence: 99%
“…The GalHexNAcPs from C. perfringens ATCC13124 and Propionibacterium acnes JCM6425 are specific for GNB, and they are named GNB phosphorylase. 98,99) Since C. perfringens strains usually colonize the human GIT along with bifidobacteria, the inability of this pathogen to utilize LNB is an feature important to the prebiotic effect of LNB. P. acnes is a skin-commensal bacterium that causes skin diseases such as acne.…”
Section: Glnbpmentioning
confidence: 99%
“…The concentration of Pi was measured as previously described. 16) The K values were calculated using the initial substrate concentrations and the Pi concentration in equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…The results are given in Table 1. The K values for the syntheses of LNB and GNB 16) were significantly higher than that of GalRha, suggesting that the difference in yield is explainable by the difference in the equilibria of the phosphorolyses. The difference in equilibrium cannot be explained by the difference in the 1!3 and 1!4 linkages, because the K value of GalRha was close to that of D-galactosyl-1!3-D-glucose.…”
Section: Equilibrium Of the Reactionmentioning
confidence: 96%
See 1 more Smart Citation